A molecular phylogeny of African Dainty Frogs, with the description of four new species (Anura: Pyxicephalidae: Cacosternum) - Channing, Alan; Schmitz, Andreas; Burger, Marius; Kielgast, Jos (Zootaxa, 2013)
We examined specimens from all eleven described species of African Dainty Frogs, Cacosternum. Advertisement calls, 16S and tyr sequences were obtained from voucher specimens of all known species plus undescribed taxa. A phylogenetic analysis indicated that there were 15 species. We describe four new species from South Africa that can be diagnosed by their advertisement calls: Cacosternum aggestum sp. nov. from the interior of the south-western Cape, the large C. nanogularum sp. nov. from KwaZulu-Natal, C. australis sp. nov. from the Western Cape Province and C. rhythmum sp. nov. from the KwaZulu-Natal midlands. Cacosternum schebeni is confirmed as a junior synonym of C. boettgeri, and we agree that C. poyntoni is a junior synonym of C. nanum. The populations of dainty frogs on the Ethiopian highlands remain to be investigated. Shared tyr haplotypes occur between species that are not necessarily closely related, but always sympatric, at least in the recent past. This is evidence for hybridisation that requires further investigation. A provisional identification key to the species is provided.